LINKING EMOTIONAL INTELLIGENCE AND CAREER DEVELOPMENT TO EMPLOYEE PERFORMANCE: THE ROLE OF EMPLOYEE ENGAGEMENT - Maulana, Nanang; Setiani, Setiani (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
This study analyzes the influence of emotional intelligence and career development on employee performance, with employee engagement as a mediating variable at the Office of Cooperatives, SMEs, and Manpower in Pamekasan Regency. A quantitative approach was employed with a sample of 76 respondents, selected using purposive sampling. Data were collected through questionnaires and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS) with SmartPLS 4.1. The results indicate that career development has a significant positive effect on employee performance and engagement. Emotional intelligence significantly influences employee engagement but does not directly affect employee performance. Employee engagement plays a mediating role between career development and employee performance. This research contributes to human resource management literature, emphasizing the importance of emotional intelligence and career development in enhancing employee performance through engagement.